Taxonomic rearrangements and typifications in Myrcia sect. Tomentosae (Myrteae, Myrtaceae) - de Lannoy, Laura C.; Goldenberg, Renato; Lima, Duane F. (Phytotaxa, 2019)
Myrcia sect. Tomentosae is morphologically easily distinguished from the other sections of Myrcia by the buds constricted below the ovary and calyx lobes reflexed at anthesis, but the specific limits within the group are not always clear. Inside this section, Myrcia lajeana, M. laruotteana, M. selloi and M. tomentosa form a species complex distributed mainly in central, southeastern and southern Brazil, but with some specimens collected in neighboring countries. Characters such as indumentum density, leaf shape, size and venation, bracteoles size, and persistence or not of the calyx lobes in the fruits are used to distinguish these species but are highly variable and many individuals with intermediate states can be found. Recent genetic studies showed this complex as separated in two big genetic pools, one containing only M. tomentosa and the other with M. lajeana, M. laruotteana and M. selloi mixed together. Based on these results and additional morphological and literature analyses, we propose here a new taxonomic arrangement of the complex with the synonymization of M. laruotteana and M. lajeana under M. selloi. Moreover, 16 lectotypes and 3 neotypes are here selected, and notes on morphology are presented.